Engineering Cell-permeable Protein - Münst, Bernhard (MyJove Corporation, 2009)
The protein transduction technique enables the direct delivery of biologically active material into mammalian cells [for review see (1,2)]. For this one can make use of the translocating ability of so-called cell penetrating peptides (CPPs), also designated as protein transduction domains (PTDs). The TAT-CPP derived from the human immunodeficiency virus type 1 (HIV-1) Tat (trans-activator of transcription) protein has been widely used. The positively charged TAT promotes cell permeability thereby overcoming the barriers of the cellular membrane by endocytosis or/and direct membrane penetration(2). In combination with a nuclear localization signal (NLS) fusion proteins are able to enter the nucleus exhibiting functionality. Our video presentation demonstrates, as an exemplification for the engineering of cell-permeable proteins, the construction, production and application of a cell-permeable version of the DNA-modifying enzyme Cre. Cre is a site-specific recombinase that is able to recognize and recombine 34 base pair loxP sites in mammalian cells in vitro and in vivo. Therefore the Cre/loxP system is widely used to conditionally induce mutations in the genome of living cells(3,4). The delivery of active Cre recombinase to cells, however, represents a limitation. We describe the pSESAME vector system, which allows a direct insertion of the gene-of-interest and provides a platform to rapidly clone different domains and tags used within the vector in a convenient and standardized manner. Rearranging of the different tags has been shown to modify the biochemical properties of the fusion proteins providing a possibility to achieve higher yield and better solubility. We demonstrate how to express and purify recombinant cell-permeant proteins in and from E. coli. The functionality of the recombinant Cre protein is finally validated in cell culture by assessing its intracellular recombinase activity.